A Qualitative Study to Explore Ambiguous Loss and Belonging in Foster Care - (:unkn) unknown (My University, 2016)
The imminent threats to a child’s physical and mental health from dangerous or dysfunctional family systems result in children being placed in foster care, often for extended periods of time. With increased physical, mental and developmental health needs identified compared to non- fostered peers, it is important to better understand the experiences of foster care. The purpose of this study was to explore ambiguous loss and belonging within the experience of foster care. Using photo elicitation techniques and repeated in depth interviews, this qualitative study explored the foster care experiences of 10 foster care alumni, aged 18 – 23 years old. Data from 22 interviews evolved into six major themes: 1. Belonging, 2. Moving...Again, 3. Ambiguous Loss, 4. I am Different, 5. I am Responsible, and 6. Gaining Perspective. Four major conclusions developed from this study: 1. A consistent and strong sense of belonging while in foster care may be difficult to achieve, 2. Adolescents in foster care feel different and are different from their peers, 3. Adolescent responsibilities come early for adolescents in foster care, potentially foreclosing opportunities for an emerging adulthood, and 4. As time separates them from foster care, young adult alumni tend to develop new perspectives on their foster care experiences. Practice implications from this study include improving screening for belonging, as belonging has been found to be protective against some mental health issues, supporting foster children experiencing ambiguous loss, and including multidisciplinary care including social workers, health care providers, school personnel and child advocates. Implications for further research include initiating cohort studies to examine issues more common in foster children compared to their non-fostered peers, measurement of the impact of support groups for foster children while in foster care, and quantitative measurement of the association and impact of ambiguous loss on belonging. Even with the difficulties experienced in foster care, the majority of participants perceived foster care to be a positive experience with a positive impact on their lives both while in foster care and as foster care alumni.
Keywords: Ambiguous Loss; Belonging; Foster Care; Foster Care Alumni